Moral Degradation of Manners Among Public Junior High School Students - Saputra, Kiki; Moeis, Isnarmi; Suryanef, Suryanef; Wirdanengsih, Wirdanengsih (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study is to describe the various forms of moral degradation in students' Manners behavior in Junior High School in Padang City, as well as the factors that influence it. This research uses a qualitative approach. The research sample was purposively selected with the consideration that the data source has relevant knowledge related to the phenomenon under study. The data collection techniques used included observation, interviews, and document analysis. Data validity was checked through triangulation of data sources. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The subjects in this study were junior high school students and teachers where this research took place. This research was conducted in the even semester of the 2023/2024 academic year. The results of the study obtained conclusions, first, the forms of moral degradation of manners of junior high school students in Padang City, namely: Students do not respect teachers, Students say dirty words, Students interrupt other people's opinions, Do not ask permission to enter the classroom, Disturb other students when they are learning. Second, the degradation of moral manners of junior high school students in Padang City is influenced by two factors, namely Internal factors and factors from within the students themselves. External factors are school environment, family environment, community environment, and peers.